2018
DOI: 10.1016/j.autcon.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for implementing building information modelling (BIM): A longitudinal review

Abstract: Although building information modelling (BIM) is ubiquitous within the construction industry, a review analysis on critical success factors (CSFs) used to measure successful BIM implementation is not well established. This research conducts a comprehensive review and interpretivist study of published studies on CSFs for BIM implementation during the period 2005 to 2015. Analysis reveals that some countries (e.g. USA, UK and South Korea) have developed clear CSFs for measuring successful BIM implementation, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 89 publications
3
152
0
10
Order By: Relevance
“…This method can streamline data transformation for a project and offer feedback to both tools. From the perspective of sustainable design, Antwi (2017) investigated awareness with actual applications of BIM technology in sustainable construction and found that the BIM application can save the construction cost and improve the working efficiency [49].…”
Section: Bim In Sustainable Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method can streamline data transformation for a project and offer feedback to both tools. From the perspective of sustainable design, Antwi (2017) investigated awareness with actual applications of BIM technology in sustainable construction and found that the BIM application can save the construction cost and improve the working efficiency [49].…”
Section: Bim In Sustainable Constructionmentioning
confidence: 99%
“…Donya (2016) conducted research from the perspective of BIM technology adoption risk, which invited United Arab Emirates (UAE) construction practitioners to perform a BIM technology application behavior survey and effective analysis of the data [33]. The effect of the UAE BIM technology application on the main risk factors was observed and relevant improvement recommendations were proposed [49]. BIM application satisfaction refers to the use of individual psychological acceptance of BIM technology and can be used to predict the effect of BIM usage behavior on the construction industry.…”
Section: Bim Application Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Two important concepts that have been developing since the 1990s will potentially have significant impacts in the delivery of construction projects, namely building information modeling (BIM) (Zhao 2017;Antwi-Afari et al 2018) and lean construction (LC) (Dave et al 2016;Sarhan et al 2017). The term "building information modelling" was first introduced into the industry in the early 2000s, from a buzzword coined by a software manufacturer with early adopters (Dainty et al 2017) and can be defined as a product, an activity, or a process (Eastman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, to improve the interoperability performance in BIM, Arayici proposed a specific approach to help develop BIM execution in construction projects [27]. In order to establish a review analysis on critical success factors, Antwi-Afari (2018) conducted a comprehensive review on study of CSFs for BIM implementation and provided valuable reference for future research [28]. Also, Tan (2019) highlighted the barriers to BIM implementation in China's prefabricated construction and offered technological and managerial solutions to improve BIM implementation in China's prefabricated construction [29].…”
Section: Constraints In Application Of Building Information Modelingmentioning
confidence: 99%